Conflict Resolution in Traditional Africa Appraising the Ubuntu Approach (Advances in Law, Pedagogy, and Multidisciplinary Humanities, 2026)
This paper examines the Ubuntu as a conflict resolution mechanism in traditional African justice system that emphasises communal co-existence and restorative justice. It is a restorative process rooted in the African humanist philosophy of I am because we are. It emphasizes interconnectedness, humanity, and collective well-being, aiming to heal, restore broken relationships and reintegrate offenders into the community, rather than merely punishing them. Over time, Ubuntu has significantly shaped conflict resolution practices across traditional African societies. The TRC of South Africa remains one of the celebrated processes that utilized and enjoys the principles of Ubuntu. This paper aims to ascertain the efficacy of Ubuntu as a conflict resolution mechanism in traditional African justice system, highlighting its socio-cultural impacts, contemporary relevance and challenges. Adopting the method of analysis, the paper argues that the strength of Ubuntu as a traditional conflict resolution mechanism lies in its ability to harmonize individual grievances with collective well-being, thus ensuring social cohesion and restorative justice. However, it reveals that Ubuntu is fraught with systemic limitations such as gender exclusion, colonial influence and limited adaptability to modern legal systems. This paper concludes by advocating for a systemic hybrid model that integrates communal and restorative elements of the Ubuntu as a traditional justice system with the formal justice systems in order to effectively address modern day conflicts.